2000
DOI: 10.1006/viro.2000.0236
|View full text |Cite
|
Sign up to set email alerts
|

An Ovine Adenovirus Vector Lacks Transforming Ability in Cells That Are Transformed by AD5 E1A/B Sequences

Abstract: Adenoviruses of the Mastadenovirus and Aviadenovirus genera are able to transform certain cell types and induce tumor formation in susceptible animals. For the mastadenoviruses the E1A/B sequences are largely responsible for these properties but E4 sequences may also be involved. The transforming sequences of the aviadenoviruses, which lack E1A/B and E4 homologues, have not yet been fully identified. The recent proposal for a third genus of adenoviruses, which apparently lack an E1A homologue and have weak E1B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
(78 reference statements)
0
15
0
Order By: Relevance
“…On the other hand, we conclude that even in the presence of viral DNA replication and synthesis of early and late gene products, OAdV replication remains blocked in nonovine cells. Together with the lack of transforming ability of OAdV (60) and the lack of transcomplementation of OAdV by Ad5 (30), our data have important positive implications for the biosafety of OAdV vectors.…”
Section: Discussionmentioning
confidence: 76%
“…On the other hand, we conclude that even in the presence of viral DNA replication and synthesis of early and late gene products, OAdV replication remains blocked in nonovine cells. Together with the lack of transforming ability of OAdV (60) and the lack of transcomplementation of OAdV by Ad5 (30), our data have important positive implications for the biosafety of OAdV vectors.…”
Section: Discussionmentioning
confidence: 76%
“…This is the subject of continuing studies, but so far it has been shown that OAdV does not replicate in a variety of cell human lines, 39 nor does it transform rodent cells that are transformed by human AdV5. 46 In addition, intravenous administration of approximately 10 11 virus particles into SCID or BALB/c mice did not cause overt toxicity. 37 Tumors based on the RM1 cell line grown in C57BL/6 mice grow far more aggressively than does prostate cancer in man.…”
Section: Discussionmentioning
confidence: 93%
“…17 As previously mentioned, the vectors have a favorable biosafety profile in human cells with respect to replication, transformation and complementation. [9][10][11][12] In addition, the legitimacy of the overall PNP-GDEPT strategy has been well documented. 17,20,21 In this study where vector was delivered intratumorally, there was no histological evidence of treatment toxicity in liver, spleen, kidney, lung or gut.…”
Section: Discussionmentioning
confidence: 99%
“…This virus is the prototype of a new genus that is distinct from the mastadenoviruses that contains all human adenoviruses. OAdV vectors escape pre-existing antibodies in sera that neutralize human adenoviruses 8 and have a favorable biosafety profile: they are replication abortive in human cells, 9 lack transforming activity 10 and are not complemented in coinfected cells by replicating human adenoviruses. 11,12 OAdV can also infect cells in human prostate biopsies maintained in organ culture.…”
Section: Introductionmentioning
confidence: 99%